Comparative Labelling and Biokinetic Studies of 99mTc-EDTA(Sn) and 99mTc-DTPA(Sn) - Agha, N.; Persson, R. B. R. (Nuklearmedizin - NuclearMedicine, 1977)
Gelchromatography column scanning has been used to study the fractions of 99mTc-pertechnetate, 99mTcchelate and reduced hydrolyzed 99mTc in preparations of 99mTc-EDTA(Sn) and 99mTc-DTPA(Sn). The labelling yield of 99mTc-EDTA(Sn) chelate was as high as 90—95% when 100 μmol EDTA · H4 and 0.5 (Amol SnCl2 was incubated with 10 ml 99mTceluate for 30—60 min at room temperature. The study of the influence of the pH-value on the fraction of 99mTc-EDTA shows that pH 2.8—2.9 gave the best labelling yield. In a comparative study of the labelling kinetics of 99mTc-EDTA(Sn) and 99mTc- DTPA(Sn) at different temperatures (7, 22 and 37°C), no significant influence on the reduction step was found. The rate constant for complex formation, however, increased more rapidly with increased temperature for 99mTc-DTPA(Sn). At room temperature only a few minutes was required to achieve a high labelling yield with 99mTc-DTPA(Sn) whereas about 60 min was required for 99mTc-EDTA(Sn). Comparative biokinetic studies in rabbits showed that the maximum activity in kidneys is achieved after 12 min with 99mTc-EDTA(Sn) but already after 6 min with 99mTc-DTPA(Sn). The long-term disappearance of 99mTc-DTPA(Sn) from the kidneys is about five times faster than that for 99mTc-EDTA(Sn).